Intra and interobserver reliability of the caliper jaw movements (Research, Society and Development, 2021)
Introduction: The analysis of mandibular movement limitations represents an important sign for understanding the diagnosis of functional alterations in the stomatognathic system. Currently, one of the main instruments used by physiotherapists, dentists and speech therapists to assess and measure mandibular movements is the caliper, a non-invasive and easy-to-use instrument that offers objective measurements in the assessment of the stomatognathic system. Objective: To assess the intra- and inter-examiner reliability of the assessment of mandibular movements using the caliper. Methods: This is a cross-sectional and comparative study carried out in individuals between 18 and 25 years old with mild or no symptoms of TMD according to the ProDTMMulti. The collection was carried out in two days of measuring the mandibular movements of opening, protrusion, right and left laterality for each examined by means of an analog plastic caliper. The agreement analysis was calculated using the Intraclass Correlation Coefficient (ICC), where a significance level of 5% was adopted. Results and Discussion: The caliper is a reliable instrument and has excellent intra-examiner reliability for almost all movements, except for left lateral deviation, which demonstrated moderate reliability and the inter-examiner reliability was moderate for most movements. Conclusion: It can be concluded that the caliper is a reliable method for intra-examiner analyses, however, this does not occur for inter-examiner assessments, where it has moderate reliability, in addition to being very useful for clinical application involving one or more examiners during the service.